2006
DOI: 10.1002/ptr.1827
|View full text |Cite
|
Sign up to set email alerts
|

A water soluble extract from Uncaria tomentosa (Cat's Claw) is a potent enhancer of DNA repair in primary organ cultures of human skin

Abstract: Cat's Claw (Uncaria tomentosa) water extracts, essentially free of oxindole alkaloids, have been shown to possess a broad spectrum of biological activity including DNA repair enhancement and antiinflammatory properties. These two biological mechanisms are key molecular targets to develop treatments that protect skin exposed to ultraviolet light from the sun. Because C-Med-100, a Cat's Claw water extract, is the only documented natural source of components that can up-regulate simultaneously both DNA repair and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 24 publications
1
27
0
1
Order By: Relevance
“…The data presented in this study on oral administration of Aqua Bimini (a quinic acid ammonium chelate) confirm earlier reports (Mammone et al, 2006;Pero et al, 2002Pero et al, , 2005Sheng et al, 2000aSheng et al, , 2000bSheng et al, , 2001Sheng et al, , 2005Åkesson et al, 2003a, 2003b, 2005 that quinic acid or quinic acid-containing water extracts possess DNA repair and/or immune enhancing properties when evaluated using serum thiol analyses as a surrogate DNA repair estimate (Figs 2-4). These data support that serum protein thiols can be increased in humans supplemented with quinic acid (Figs 2-4), and that these effects mirrored DNA repair enhancement as shown previously in other mammals.…”
Section: Discussionsupporting
confidence: 90%
“…The data presented in this study on oral administration of Aqua Bimini (a quinic acid ammonium chelate) confirm earlier reports (Mammone et al, 2006;Pero et al, 2002Pero et al, , 2005Sheng et al, 2000aSheng et al, , 2000bSheng et al, , 2001Sheng et al, , 2005Åkesson et al, 2003a, 2003b, 2005 that quinic acid or quinic acid-containing water extracts possess DNA repair and/or immune enhancing properties when evaluated using serum thiol analyses as a surrogate DNA repair estimate (Figs 2-4). These data support that serum protein thiols can be increased in humans supplemented with quinic acid (Figs 2-4), and that these effects mirrored DNA repair enhancement as shown previously in other mammals.…”
Section: Discussionsupporting
confidence: 90%
“…Uncaria tomentosa extracts can act as an antioxidant and are able to enhance DNA repair (Sandoval et al, 2000;Miller et al, 2001;Akesson et al, 2003a;Goncalves et al, 2005;Mammone et al, 2006;Pilarski et al, 2006). In vitro studies have shown that Uncaria tomentosa may have an anti-apoptotic activity in some cells, such as lymphocytes, following treatment with apoptotic inducers such as hydrogen peroxide, diphenyl-2-picrylhydrazyl, and peroxynitrite (Sheng et al, 1998;Akesson et al, 2003a,b).…”
Section: Introductionmentioning
confidence: 94%
“…Moreover, positive effects on UVB induced carcinogenesis, as well as patches induced by UVB were ameliorated with caffeine administration and topical application respectively in mice (Conney et al, 2008). In addition, co-incubation with quinic acid prevented skin death that was caused by UV damage in skin cultures (Mammone et al, 2006). …”
Section: Coffee Plantmentioning
confidence: 99%